Secrets of antiparkinson therapy - Fiszer, Urszula (Przewodnik Lekarza/Guide for GPs, 2005)
Parkinson’s disease is a common neurological disorder. The efficient therapy depends on various factors in qualifying patients for therapy. The diagnosis, appropriate drug and dose therapy, as well as patient’s characteristics should be considered here. Also the stage of the disease is very important in choosing therapy. In cases of inefficient drug therapy surgical procedures are to be considered.